Mutations in RELT cause autosomal recessive amelogenesis imperfecta. Issue 3 (21st December 2018) - Kim, Jung‐Wook; Zhang, Hong; Seymen, Figen; Koruyucu, Mine; Hu, Yuanyuan; Kang, Jenny; Kim, Youn J.; Ikeda, Atsushi; Kasimoglu, Yelda; Bayram, Merve; Zhang, Chuhua; Kawasaki, Kazuhiko; et al.
Abstract : Amelogenesis imperfecta (AI) is a collection of isolated (non‐syndromic) inherited diseases affecting dental enamel formation or a clinical phenotype in syndromic conditions. We characterized three consanguineous AI families with generalized irregular hypoplastic enamel with rapid attrition that perfectly segregated with homozygous defects in a novel gene: RELT that is a member of the tumor necrosis factor receptor superfamily (TNFRSF). RNAscope in situ hybridization of wild‐type mouse molars and incisors showed specific Relt mRNA expression by secretory stage ameloblasts and by odontoblasts. Relt −/− mice generated by CRISPR/Cas9 exhibited incisor and molar enamel malformations. Relt −/− enamel had a rough surface and underwent rapid attrition. Normally unmineralized spaces in the deep enamel near the dentino‐enamel junction (DEJ) were as highly mineralized as the adjacent enamel, which likely altered the mechanical properties of the DEJ. Phylogenetic analyses showed the existence of selective pressure on RELT gene outside of tooth development, indicating that the human condition may be syndromic, which possibly explains the history of small stature and severe childhood infections in two of the probands. Knowing a TNFRSF member is critical during the secretory stage of enamel formation advances our understanding of amelogenesis and improves our ability to diagnose human conditions featuring enamel malformations. Abstract : Three consanguineous families with homozygous RELT mutations segregating with a hypomineralized enamel phenotype (A); Specific Relt expression by odontoblasts and secretory stage ameloblasts (B); Enamel defects in the Relt−/− mouse incisors (C).